RELATIONSHIP BETWEEN DEPRESSION LEVEL AND SELF-CARE IN THE ELDERLY AT PSTW SABAI NAN ALUIH SICINCIN - Madoni, Abri (Ensiklopedia of Journal, 2021)
Self-care in the elderly can change due to life situations. Motivation is a psychological process that reflects the interaction between attitudes, needs, perceptions, and decisions that occur in a person. The purpose of this study was to determine the relationship between depression levels and self-care in the elderly at PSTW Sabai Nan Aluih Sicincin. The type of research is quantitative research with the design of this study is a cross sectional study. The population is all the elderly who are in the Tresna Werdha Sabai Nan Aluih Sicincin Social Institution with a total of 110 people with 52 samples. The sampling method is using simple random sampling technique, the research was conducted on and research instruments using a questionnaire. Based on the results of the study, it was obtained that less than half (44.2%) of the elderly had low motivation, more than half (59.6%) of the elderly were unable to perform self-care and there was a relationship between motivation and self-care in the elderly at PSTW Sabai Nan Aluih Sicincin.It is hoped that the officers at PSWT Sabai Nan Aluih will be able to provide more motivation to the elderly such as giving awards and flattery to the elderly if they are able to take care of themselves, so that it becomes enthusiasm and motivation for the elderly to take care of themselves.